2003
DOI: 10.1177/00207640030493006
|View full text |Cite
|
Sign up to set email alerts
|

Drowning Your Sorrows? Attitudes Towards Alcohol in UK Jews and Protestants: A Thematic Analysis

Abstract: The themes identified are not measurable using published research instruments. Alcohol-related behaviour may be a feature of Jewish identity. The beliefs identified are consistent with the alcohol-depression hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Thus, Judaism supports and prescribes the controlled use of alcohol [1]. This has been suggested as an explanation for the overall lower levels of alcohol use and abuse among Jews [1][2][3][4][5].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Judaism supports and prescribes the controlled use of alcohol [1]. This has been suggested as an explanation for the overall lower levels of alcohol use and abuse among Jews [1][2][3][4][5].…”
Section: Open Accessmentioning
confidence: 99%
“…Jews hold more pejorative beliefs about alcohol use than do Protestants [26], and excessive drinking was considered to be an out-group characteristic by the Jewish community [1]. Jews reported negative stereotypes about drinking and drunkenness among the rest of (non-Jewish) society, while people of Protestant background were more likely to say that alcohol enabled relaxation and a reduction of worry and tension [3]: "It's something that non-Jews do generally therefore it is frowned upon in the Jewish community" (Jewish man); "If you do go to the pub, you expect that there will be a lot of drunk people around and beer flying" (Jewish woman); "It can lead to abuse or to violence…it can cause husbands hitting wives…destroying furniture, things like this…attacking wives and children" (Jewish woman);…”
Section: Community Beliefs and Attitudesmentioning
confidence: 99%
“…We will focus on religiously based norms of behavior and belief that affect health and well-being. For example, Loewenthal et al (2003aLoewenthal et al ( , 2003b examined the beliefs held by Jews and Protestants in the United Kingdom regarding alcohol use. Jews reported consuming less alcohol than did Protestants and also reported less favorable attitudes regarding drinking, being drunk, and social and recreational drinking.…”
Section: Religion-as-culture and Implications For Health And Well-beingmentioning
confidence: 99%
“…Thus, for mental health authorities, knowledge of the public's attitude to community psychiatry is important when planning community mental health services. Various parameters were found to influence the public's attitude to psychiatry (Aghanwa, 2004;Al Krenawi et al, 2004;Aydin et al, 2003;Corrigan et al, 2003;Furnham & Buck, 2003;Kocmur & Dernovsek, 2003;Loewenthal et al, 2003;Magliano et al, 2004;Mallett et al, 2004). Previous studies have identified demographic factors as having an influence on the public's attitude to community psychiatry (Brockington et al, 1993;Wolff et al, 1996).…”
Section: Introductionmentioning
confidence: 99%